Mortar functionalized with silver nanoparticles for antifungal activity - Paiva, Fábio Friol Guedes de; Tamashiro, Jacqueline Roberta; Silva, Lucas Henrique Pereira; dos Santos, Laira Sabrina Rosa; Gouveia, Jaqueline Stabile; Magdalena, Aroldo Geraldo [UNESP]; Baffa, Oswaldo; Pires, Regina Helena; Kinoshita, Angela (Elsevier, 2024)
Building materials are susceptible to fungus attack, leading to structural and aesthetic problems. Nanotechnology has enabled the development of innovative products with unique properties, including antimicrobial capabilities. Although the antimicrobial potential of AgNPs is already known, research on the application of AgNPs in cementitious materials and the behavior in prevention of fungal biofilm formation are still an extremely limited topic. Specifically, against the fungi presented in this paper there are no reports. In this work, two types of composites were formulated using AgNPs (108 μg/mL and 54 μg/mL) and tested against Aspergillus and Fusarium biofilms, fungi causing losses during grain storage. The AgNPs composites showed strong antifungal capacity, reaching up to 99 % reduction of Fusarium and 57 % of Aspergillus biofilms. The reduction in the amount of Fusarium biofilm (AgNPs 108 μg/mL) is proven by SEM images. No Ag leaching and interference in the mechanical properties of 54 μg/mL mortar were observed. Thus, a promising solution is presented for applications in agribusiness. And also, with a small 6.22 % increase in cost, this innovative mortar can contribute to mitigate post-harvest losses caused by fungal contamination. Its significant role in preserving the integrity and quality of stored grains contributes significantly to food security and sustainability.
Keywords: Antifungal; Mechanical resistance; Mortar; Silver nanoparticles